Planning for Integral Development. Public Policies, Economic Growth and Social Improvements in Santa Rosa (Ecuador) - Prada-Trigo, José (Journal of Tourism, Sustainability and Well-being, 2014)
Ecuador is immersed, since the adoption of the 2008 Constitution, in a process of economic, social and political changes, following the steps on their path to a more equal, post-extractive and democratic society. The main tool for this purpose, the National Strategy for the «Buen Vivir» (Good living) and the Change in the Production Model emphasizes new ways for producing, consumption and self-organization. Although Ecuadorian Constitution comprises these ideas and the Ecuadorian Government has promoted different programs and strategies, there is a limited analysis about the local manifestations of these policies. In this way, this paper proposes a study of the local strategies developed in a medium-size city in the south of Ecuador through the analysis of the local networks and the initiatives of local actors for developing strategies oriented to this end. Interviews and statistical data (demographic, economic and social data mainly) are used to confirm the level of accomplishment of these objectives. Thus, the existing local networks and the path of the city of Santa Rosa may explain the different level of recent socioeconomic changes taken place at local level instead of Central government policies.